Modeling techniques to study CO2-injection induced micro-seismicity. (November 2015) - Carcione, José M.; Da Col, Federico; Currenti, Gilda; Cantucci, Barbara
Abstract : Highlights: We model the pore-pressure build-up due to the injection of CO2 in an aquifer. Failure criteria are established by emission of tensile and shear micro-earthquakes. A poroelasticity model is used to obtain the hydraulic diffusivity. Wave propagation of P and S waves is simulated with a full-wave solver. A reverse-time migration algorithm is outlined to locate asynchronous sources. Abstract: CO2 injection in saline aquifers is one solution to avoid the emission of this greenhouse gas to the atmosphere. This process induces a pore-pressure build-up around the borehole that generates tensile and shear micro-earthquakes which emit P and S waves if given pressure thresholds are exceeded. Here, we develop a simple model to simulate micro-seismicity in a layer saturated with brine, based on an analytical solution of pressure diffusion and an emission criterion for P and S waves. The model is based on poroelasticity and allows us to obtain estimations of the hydraulic diffusivity on the basis of the location of the micro-earthquakes (defining the CO2 plume) and the triggering time. Wave propagation of P and S waves is simulated with a full-wave solver, where each emission point is a source proportional to the difference of the pore pressure and the tensile and shear pressure thresholds. Finally a reverse-time migration algorithm is outlined to locate the asynchronous sources induced by the fluid flow, determinated by the maximum amplitude at each cell versus the back propagation time.